A structural model of demand for apprentices - Samuel Muehlemann; Juerg Schweri; Rainer Winkelmann; Stefan C. Wolter (Center for Economic Studies and ifo Institute (CESifo), 2005)
It is a widely held opinion that apprenticeship training represents a net investment for training firms, and that therefore firms only train if they have the possibility to recoup these investments after the training period. A recent study using a new firm-level dataset for Switzerland showed, however, that for 60 percent of the firms, the apprenticeship training itself does not result in net cost. In this context it seems important to examine the question whether the potential net cost of training (during the training period) are a major determinant for the demand for apprentices. Different count data models, in particular hurdle models, are used to estimate the effect of net cost on the demand for apprentices. The results show that the net cost has a significant impact on the training decision but no significant influence on the demand for apprentices, once the firm has decided to train. For policy purposes, these results indicate that subsidies for firms that already train apprentices would not boost the demand for apprentices.
Keywords: C25; J24; 330; apprenticeship training; count data; probit-Poisson-log-normal model; Switzerland; Auszubildende; Arbeitsnachfrage; Lehrstellenmarkt; Betriebliche Berufsausbildung; Bildungsinvestition; Kosten; Schätzung; Schweiz